Runoff modeling, taking into consideration snow melts accumulation processes - Dumbrauskas, Antanas; Raškinienė, Danutė (Lietuvos matematikos rinkinys, 2000)
A rainfall-runoff model is developed to simulate snowmelt process during spring floods. The snowmelt accumulation model is based on a modified degree-day method and provides the equivalent amount of melted accumulated water for small grid cell of the catchments considered. The interval of time there is 1 hour instead of one day. Water movement through the snow pack is very complicated process. It was split into three phases in relation to air and snow surface temperature. As the result there was developed very simple structure of snowmelt model, which needs a limited amount of input data.